Descartes as an Ethical Perfectionist - Frans Svensson (Journal of Modern Philosophy)
My main concern in this paper is to develop and defend an account of why we ought to devote our lives to virtue—of the ground or reason for why we ought to do so—according to René Descartes. On my account, the answer is that we thereby, and indeed only thereby, do everything in our power to promote our own degree of intrinsic perfection or goodness (Descartes uses these terms interchangeably). Descartes’s moral philosophy, as I understand it, thus constitutes a form of ethical perfectionism. While I am not the first to interpret Descartes as an ethical perfectionist, there is as of yet no detailed account in the literature of what his particular form of ethical perfectionism would then entail. This is something that I hope to remedy here.